Establishing a benchmark of diversity, equity, inclusion and workforce engagement in radiation oncology in Europe – An ESTRO collaborative project. (June 2022) - Gasnier, Anne; Jereczek-Fossa, Barbara Alicja; Pepa, Matteo; Bagnardi, Vincenzo; Frassoni, Samuele; Perryck, Sophie; Spalek, Mateusz; Petit, Steven F.; Bertholet, Jenny; Dubois, Ludwig J.; Franco, Pierfrancesco
Highlights: Diversity, Equity & Inclusion is linked to improved care, research & staff engagement. A survey among radiation oncology professionals was conducted in Europe. The questionnaire was adapted from the Diversity Engagement Survey. Inclusion scores were lower than American benchmark data for most factors. Inclusion scores were lower for respondents who felt they belonged to minority groups. Abstract: Background and purpose: Diversity, Equity and Inclusion (DEI) in the medical workforce is linked to improved patient care and innovation, as well as employee retention and engagement. The European Society for Radiotherapy and Oncology launched a survey to provide a benchmark of DEI and engagement among radiation oncology (RO) professionals in Europe. Methods: An anonymous survey was disseminated among RO professionals in Europe. The survey collected demographics and professional information, and participants were asked if they felt they belonged to a minority group. A DEI and workforce engagement questionnaire by Person et al. evaluated 8 inclusion factors. A favourable score was calculated by adding the percentage of "strongly agreed" or "agreed" answers. Results: A total of 812 complete responses were received from 35 European countries . 21% of respondents felt they belonged to a minority group, mostly based on race/ethnicity (5.9%), nationality (4.8%) and age (4.3%). Compared to benchmark data from the United States, scores were lower for most inclusion factors, and to a greater extent for minority groups. The overall favourable score was 58% for those belonging to a minority group, significantly lower than for other respondents (71%, p  < 0.001). Those belonging to a minority group because of their gender or age had the lowest overall favourable score (47% and 51% respectively). Conclusions: Our work indicates that actions to improve DEI and workforce engagement among RO professionals in Europe are urgently needed, in particular among minority groups. This would potentially improve employee wellbeing and retention, promoting high quality care and innovation.